An emphasis study on residual engineering properties of fly ash concrete elevated temperature / Nurizaty Zuhan ... [et al.] - Zuhan, Nurizaty; Mohd Saman, Hamidah; Ab. Kadir, Mariyana Aida; M. Ali Masto, M. Najmi; Shek, Poi Ngian (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
The paper examines the properties of fly ash as partial cement replacement in normal strength concrete at ambient and elevated temperature. The properties of fly ash class F was chemically investigated. Behaviour of concrete containing fly ash subjected to elevated temperature 200 ºC up to 600 ºC at temperature rate of 2.78 ºC/min is investigated mechanically and microstructurally. Physically, fly ash concrete changed colour to brown at 400ºC and to whitish grey at 600 ºC, which is similar to normal concrete. At 600ºC, the residual compressive strength of fly ash concrete was slightly higher than normal concrete with a strength reduction of 13.18% and 45.22%, respectively. At 400 ºC, fly ash concrete has better splitting tensile strength than normal concrete with strength reduction of 28.81% and 43.26%, respectively. Thus, the use of fly ash as cement replacement in fly ash concrete improves concrete performance after exposed to elevated temperatures. Based on Field Emission Scanning Electron Microscopy (FESEM) and Energy Dispersive X-Ray (EDX), fly ash concrete performed better thermally proven by the formation of ettringite. In conclusion, the utilization of fly ash as a replacement for Ordinary Portland cement (OPC) at elevated temperatures is a good innovation for concrete performance.